SCIENTIFIC RESEARCH ON TOPICAL ANESTHESIA IN PERMANENT MAKEUP: RISK ASSESSMENT AND PRESENTATION OF A NEW METHOD - Хвачак, Юлія (SWorldJournal, 2025)
The paper addresses the current issue of comprehensively assessing the safety and effectiveness of anesthesia application methods. Topical anesthesia is a crucial stage in the permanent makeup procedure, as it determines the level of patient comfort, the